LITERATURE REVIEW FACTORS AFFECTING TEACHER PERFORMANCE: HR PLANNING, RECRUITMENT AND SYSTEMATIC THINKING - Nurmadiah, Nurmadiah; Kemas Imron Rosyadi (Dinasti International Journal of Digital Business Management, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence teacher performance, namely: HR Planning, Recruitment and Systematic Thinking, a study of Human Resource Management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) HR planning affects teacher performance; 2) Recruitment has an effect on Teacher Performance; and 3) Systematic Thinking has an effect on Teacher Performance.